Exploiting induced and natural epigenetic variation for crop improvement - Springer, N.M.; Schmitz, R.J.
Plant breeding has traditionally relied on combining the genetic diversity present within a species to develop combinations of alleles that provide desired traits. Epigenetic diversity may provide additional sources of variation within a species that could be captured or created for crop improvement. It will be important to understand the sources of epigenetic variation and the stability of newly formed epigenetic variants over generations to fully use the potential of epigenetic variation to improve crops. The development and application of methods for widespread epigenome profiling and engineering may generate new avenues for using the full potential of epigenetics in crop improvement.
Keywords: CROP; DNA METHYLATION; EPIGENETICS; GENETIC VARIATION; GENETICS; GROWTH, DEVELOPMENT AND AGING; PHYSIOLOGY; PLANT BREEDING; PLANT CHROMOSOME